Rubber Toughened Polyamide 6/ Polypropylene Nanocomposites: Mechanical, Thermal And Morphological Properties - Wahit, Mat Uzir (2006)
Rubber-toughened nanocomposites (RTNC) consisting series of compatibilized polyamide 6 / polypropylene (PA6/PP) blends, of composition 100/0, 70/30, 50/50, 30/70 and 0/100, polyethylene-octene elastomer (POE) and organophilic modified montmorillonite (organoclay) were produced by melt compounding followed by injection moulding. Polypropylene grafted maleic anhyride (PPgMA) was used as compatibilizer. Subsequently, for PA6/PP (70/30), the POE and organoclay loading was varied between 5 and 20 wt% and 2-6 wt%, respectively. For the optimum particles dispersed in the PA6 matrix, was characterized by scanning electron of a formulation, four different types of elastomer were incorporated into the blends i.e. ethylene-octene elastomer (POE), ethylene-propylene elastomer (EPR), maleated POE (POEgMAH) and maleated EPR (EPRgMAH). For the selected formulation, the nanocomposites were also prepared through different mixing sequence of melt intercalation i.e. direct, two times and two steps method. The mechanical properties were studied through tensile, flexural, Izod impact and fracture toughness testing. The morphology, essentially comprised of PP and POE microscopy (SEM). Wide angle X-ray diffraction (XRD) was used to characterize the formation of the nanocomposites. The thermal properties were characterized by using differential scanning calorimeter (DSC) and thermogravimetry analysis (TGA). The dynamic mechanical were analyzed by using dynamic mechanical thermal analyzer (DMTA).